Pre-stroke Physical Inactivity and Stroke Severity in Male and Female Patients - Salmantabar, Pegah; Abzhandadze, Tamar; Viktorisson, Adam; Reinholdsson, Malin; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2022)
Introduction: Females experience more severe ischemic strokes than do males. A higher pre-stroke physical activity level is associated with less severe stroke. The primary aim of this study was to explore the association between pre-stroke physical inactivity and stroke severity in male and female patients. Methods: This was a retrospective, registry-based study. The data were retrieved from two stroke registries from 2014 to 2019. The primary explanatory variable was physical activity level before the stroke, assessed using the Saltin-Grimby Physical Activity Level Scale. The outcome was moderate to severe stroke at hospital admission, assessed using the National Institutes of Health Stroke Scale (NIHSS). A moderate to severe stroke was defined as an NIHSS score of ≥ 6. Binary logistic regression analysis was performed to explore if physical inactivity before the stroke could explain stroke severity in male and female patients. Results: In total, we included 4535 patients with ischemic stroke. Female patients (n = 2145) had a mean age of 76 years, 35% had a moderate to severe stroke, and 64% were physically inactive pre-stroke. Male patients (n = 2390) had a mean age of 72 years, 25% had a moderate to severe stroke, and 49% were physically inactive pre-stroke. Physical inactivity was associated with higher odds for moderate to severe stroke in both sexes (females’ odds ratio [OR], 2.7, 95% confidence interval [CI] 2.2–3.3, p < 0.001 and males’ OR, 2.06, 95% CI 1.7–2.5, p <0.001). The association remained significant in adjusted models. Conclusions: Physically inactive females and males had higher odds of experiencing a moderate to severe stroke. However, the OR of female patients was somewhat higher than that of male patients.